Anomali Pada Bursa Efek Indonesia - Eka Nuraini Rachmawati; Restu Hayati; Linda Hetri Suriyanti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
Anomaly occurs when the return earned is not in accordance with the value it should be and makes the capital market inefficient. The anomalies tested were the day of The Week Effect, Week Four Effect, January Effect and Sell In May And Go Away. The population used is 144 Manufacturing stocks listed on the Indonesia Stock Exchange. The data analysis technique used to prove the occurrence of anomalies is the Z-value large sample difference test. This study examines anomalies not only in the short term, but also in the long term. The research results prove that there are no anomalies in manufacturing companies in Indonesia in the long run. In the short term, anomalies can occur, namely the sell in May effect in 2015 and the January Effect in 2017 on manufacturing companies on the Indonesia Stock Exchange.